Case Report: Vortioxetine in the Treatment of Depressive Symptoms in Patients With Epilepsy—Case Series - Siwek, Marcin; Gorostowicz, Aleksandra; Bosak, Magdalena; Dudek, Dominika (Frontiers in Pharmacology, 2022)
Epilepsy and depression are both serious and potentially disabling conditions which often coexist – bidirectional relationship between the two disorders has been observed. Comorbidity between depression and epilepsy can be attributed to: underlying common pathophysiological mechanisms, psychiatric side effect of antiepileptic medications and psychological response to stress in people with chronic, neurological condition. Despite high prevalence of depressive symptoms in patients with epilepsy, current evidence of the effectiveness of antidepressant therapy in this group of patients is very limited. Vortioxetine is an antidepressant with multimodal activity, very good treatment tolerability, low risk of inducing pharmacokinetic interactions, relative safety of treatment in patients with somatic comorbidities, low risk of causing: sedation, sexual dysfunctions and metabolic side effects. Vortioxetine seems to be a promising treatment option for depressed patients with cognitive dysfunctions, anhedonia and anxiety. In this case series, we report nine cases of patients with epilepsy and depressive symptoms treated with vortioxetine. Seven cases are patients with secondary focal and generalized epilepsy and two with unclassified epilepsy. Three patients presented with depressive episode in the course of bipolar disorder and six patients had depressive symptoms due to organic mood disorder. The dose range of vortioxetine was between 10 and 20 mg. In all of the presented cases effectiveness and tolerability of treatment were very good. Remission of depressive symptoms was achieved in all patients. No epilepsy seizures after switch to vortioxetine were observed in seven cases. In two patients seizures occurred during the first months of vortioxetine treatment but this most probably was due to suboptimal antiepileptic treatment – satisfactory seizure control was achieved after optimization of antiepileptic pharmacotherapy. Vortioxetine was discontinued in two of the presented cases due to pregnancy planning. The duration of observation period during vortioxetine therapy ranged from 2 to 48 months. In conclusions, vortioxetine can be a promising treatment option in patients with epilepsy and comorbid depressive symptoms.